1999
DOI: 10.1097/00001756-199907130-00001
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-band MEG activity to coherent motion depends on task-driven attention

Abstract: We examined gamma-band magnetoencephalographic (MEG) activity in humans manipulating attention to visual stimuli by auditory distractors. After exposure to both visual and auditory noise (a baseline), subjects attended to the first of two stimuli (either regular motion of bars or a tone sequence) presented asynchronously, and responded to its offset. A spectral power analysis revealed an increased, relative to baseline, 40 Hz MEG response to attended coherent motion. The enhancement occurred within the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 2 publications
4
20
0
Order By: Relevance
“…Keil et al, 1999;Rodriguez et al, 1999;TallonBaudry, Bertrand, Wienbruch, Ross, & Pantev, 1997;Müller et al, 1996;Müller, Junghöfer, Elbert, & Rockstroh, 1997;Lutzenberger et al, 1995;Tallon, Bertrand, Bouchet, & Pernier, 1995). In our previous experiments we have demonstrated that induced GBRs in the human EEG were significantly increased when subjects attended to a visual stimulus at a certain location compared to when that stimulus was unattended (Müller, Gruber, & Keil, 2000;Gruber et al, 1999), which was confirmed and extended to cross-modal attention in a recent MEG study (Sokolov et al, 1999). Animal studies based on tactile attention suggested that attending to a stimulus is linked to an increase of synchrony of neural activity in the somatosensory and motor cortex (Murthy & Fetz, 1992;Murthy, Aoki, & Fetz, 1994) and between cells in the secondary somatosensory cortex (Steinmetz et al, 2000) of the monkey brain.…”
Section: Introductionsupporting
confidence: 71%
“…Keil et al, 1999;Rodriguez et al, 1999;TallonBaudry, Bertrand, Wienbruch, Ross, & Pantev, 1997;Müller et al, 1996;Müller, Junghöfer, Elbert, & Rockstroh, 1997;Lutzenberger et al, 1995;Tallon, Bertrand, Bouchet, & Pernier, 1995). In our previous experiments we have demonstrated that induced GBRs in the human EEG were significantly increased when subjects attended to a visual stimulus at a certain location compared to when that stimulus was unattended (Müller, Gruber, & Keil, 2000;Gruber et al, 1999), which was confirmed and extended to cross-modal attention in a recent MEG study (Sokolov et al, 1999). Animal studies based on tactile attention suggested that attending to a stimulus is linked to an increase of synchrony of neural activity in the somatosensory and motor cortex (Murthy & Fetz, 1992;Murthy, Aoki, & Fetz, 1994) and between cells in the secondary somatosensory cortex (Steinmetz et al, 2000) of the monkey brain.…”
Section: Introductionsupporting
confidence: 71%
“…Advances in neuroimaging technologies such as the hemodynamic functional imaging methodologies (fMRI and PET) and the ability to conduct high-density multi-channel electro- and magneto- encephalographic recordings (EEG and MEG) have allowed for unprecedented advances in our understanding of the physiology of human selective attention. This report specifically addresses evidence for the role of oscillatory brain mechanisms in selective attention (e.g., Vanni et al, 1997; Foxe et al, 1998; Gruber et al, 1999; Shibata et al, 1999; Sokolov et al, 1999; Worden et al, 2000; Sauseng et al, 2005; Yamagishi et al, 2005; Kelly et al, 2006; Thut et al, 2006; Rihs et al, 2007; Snyder and Foxe, 2010). …”
mentioning
confidence: 86%
“…Some evidence suggests that one correlate of the first variety of attention, enhancement of neural processing for stimuli at the focus of attention, is the selective modulation of evoked gamma-band oscillatory activity (e.g., Gruber et al, 1999; Shibata et al, 1999; Sokolov et al, 1999; Fries et al, 2001). The evoked gamma-band response has been implicated as a neural mechanism for feature binding (e.g., Singer, 1993, 1999), and these studies have suggested that this binding function can be selectively invoked during attention tasks.…”
mentioning
confidence: 99%
“…Fell et al (2002) reasoned that a process linked to T1 processing and indexed by the T1-related P3 impairs a T2 related process indexed by the early evoked gamma response to T2. The early evoked gamma response has been suggested to be necessary for attention allocation to a selected object and therefore for stimulus discrimination and target selection/identification (Debener, Herrmann, Kranczioch, Gembris, & Engel, 2003; Fell et al, 2002; Herrmann & Knight, 2001; Herrmann & Mecklinger, 2000, 2001; Sokolov et al, 1999; Tiitinen, May, & Näätänen, 1997; Tiitinen, Sinkkonen, May, & Näätänen, 1994). Based on the observations that (a) the AB reaches its peak at a T1-T2 interval of about 300 ms and that (b) the T1-related P3 had a peak latency of about 400 ms (McArthur, Budd, & Michie, 1999), the T2-related process was hypothesized to have a latency of about 100 ms. Because research failed to find impairments in ERPs occurring in this time period (Vogel et al, 1998), Fell et al (2002) suggested that it is the early evoked gamma response that is impaired.…”
Section: Oscillatory Activity In the Attentional Blinkmentioning
confidence: 99%